2018
DOI: 10.1016/j.jdeveco.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Saving more in groups: Field experimental evidence from Chile

Abstract: We test the impact of a peer group savings program on precautionary savings, through two randomized field experiments among 2,687 microcredit clients. The first experiment finds that the Peer Group Treatment, which combines public goal setting, monitoring in the group, and non-financial rewards, increases savings in a new savings account significantly. The number of deposits grows 3.7-fold, and the average savings balance almost doubles. In contrast, a more classical measure, a substantially increased interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(68 citation statements)
references
References 80 publications
2
65
0
1
Order By: Relevance
“…Laibson (2015) offers an analysis that shows how a combination of partial naiveté about future time inconsistency, uncertainty, and direct costs of setting up a commitment can eliminate the demand for commitment. A number of authors have argued that rotating savings and credit associations (ROSCAs), an arrangement in the developing world where group members regularly meet to contribute savings to a common pot that is disbursed to one of the members at the end of the meeting, are commitment devices to save (Ambec and Treich, 2007;Gugerty, 2007;Basu, 2011;Kast et al, 2016). Even so, alternative explanations exist; for example, ROSCAs may lock down assets and prevent other family members from claiming them (Anderson and Baland, 2002).…”
Section: Commitment Devicesmentioning
confidence: 99%
“…Laibson (2015) offers an analysis that shows how a combination of partial naiveté about future time inconsistency, uncertainty, and direct costs of setting up a commitment can eliminate the demand for commitment. A number of authors have argued that rotating savings and credit associations (ROSCAs), an arrangement in the developing world where group members regularly meet to contribute savings to a common pot that is disbursed to one of the members at the end of the meeting, are commitment devices to save (Ambec and Treich, 2007;Gugerty, 2007;Basu, 2011;Kast et al, 2016). Even so, alternative explanations exist; for example, ROSCAs may lock down assets and prevent other family members from claiming them (Anderson and Baland, 2002).…”
Section: Commitment Devicesmentioning
confidence: 99%
“…Individuals may be affected by the actions of their peers through a variety of channels. Using the example of group savings, the literature has shown that peer effects operate through channels such as (a) learning how to use financial products; (b) reminders; (c) posting a bond; or (d) reference‐dependent preferences (“keeping up with the Joneses”) (see Jack and Suri (), Cai, de Janvry, and Sadoulet (), Bryan, Karlan, and Zinman (), Kast and Pomeranz (), Beaman, Karlan, and Thuysbaert (), Beshears, Choi, Laibson, Madrian, and Milkman ( ), Munshi (), Karlan, McConnell, Mullainathan, and Zinman ( ), Bursztyn, Ederer, Ferman, and Yuchtman ( ), and Banerjee, Chandrasekhar, Duflo, and Jackson ( )). However, less has been written on whether peer effects may arise from individuals wanting to impress others through their actions.…”
Section: Introductionmentioning
confidence: 99%
“…Our intervention can be interpreted as a special kind of commitment savings device where the characteristics of the monitor determine how well it performs. Research has also shown that increased savings has numerous benefits including increased investment, working capital, income, and even labor supply, and can improve the ability for households to overcome shocks ( Dupas and Robinson (, ), Prina (), Schaner (), and Kast and Pomeranz ()). We can explore these issues in the short run (6 months) and medium run (21 months) through the lens of our study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If consumers look to financially capable peers for guidance, they may gain valuable information that helps to counter the problems that arise from imperfect optimization and be encouraged to adopt better financial behaviors. 57,58 But social comparison can also create a sense of envy or discouragement that can deter people from engaging in better financial behaviors. [59][60][61] Interventions 62 coupled with a "fresh start" decision moment to increase savings plan participation.…”
Section: Biased Judgments and Preferencesmentioning
confidence: 99%